Who are the B40 matured and older rural women related to freshwater fisheries economic sector in Kuala Krai, Kelantan? - Zainalaludin, Zumilah; Saidi, Norehan; Jamaluddin, Askiah; Zainudin, Norzalina (Human Resource Management Academic Research Society, 2023)
This study focused on MORW in FFES at Kuala Krai, Kelantan, from the B40 group of household income category who were mainly involved as trader types of value chain activities. Most women are traders, while the men are the majority operators. The predictors of B40 MORW are 'not schooling/primary education', married, and trader type of FFES value chain activities. Therefore, in Kuala Krai, married and poor MORW must be given extra focus in the poverty eradication program. The recommendation to eradicate poverty among MORW is to focus on a family business or farm-preneur “ the wives process and market the fish while the husbands produce fresh fish. There must be segregation between husband and wives' activities for the women to be empowered “ have control over their resources and decision-making power, and not involve in aquaculture farming activities with no pay. The MORW must be involved in capacity-building programs, especially in GIG Economy, to sell fish or fish-based products and financial assistance programs